Attitude toward Spirituality and Spiritual Care among Nurses, Nursing Faculty Members and Nursing Students at Jahrom University of Medical Sciences - Mahboobeh Taghizadeganzadeh; zahra Shadfard; Tahereh Abdian; Fajrieh Zahediniya; Zahra Karami (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī, 2025)
Introduction: Health is a multidimensional subject including physical, mental, social, and spiritual items. The nurses’ spirituality and provision of spiritual care are interrelated. Accordingly, this study aimed to determine the attitude toward spirituality and spiritual care among nurses, nursing faculty members, and  nursing students.